Digitalization of Service Delivery: A Social and Technological Innovation for the Enhancement of Local Government Performance in Cameroon (African Journal of Law and Politics, 2025)
Decentralization in Cameroon was motivated by the government’s quest for service delivery efficiency. However, the wave of technological advancement has proven that there is need for a shift in paradigm towards embracing digitalization in service delivery. Social innovations let by ICT use has brought greater awareness among citizens, who now need to conveniently carry out transactions and also to obtain accessible, reliable, and sustainable information from their local government. Unfortunately, this is still far from the reality of some local councils in Cameroon. Digitalization could constitute a plethora of social innovation opportunities on which local government service delivery would thrive. In spite of the opportunities that digitalization presents, there remain some constraints for it to be fully embraced. This paper examines digitalization as a social innovation for local government service delivery by discussing the context for digitalization as a social innovation for local governments in Cameroon and presents empirical evidence on the possibility for a shift in paradigm from analogue to digital considerations of information and transactional service delivery by local governments in Cameroon. Secondly, this paper examines digitalization of information and transactional services in relation to local government performance by looking at the possible role of digitalized service delivery in enhancing local government performance. It illustrates how adopting the Government to Business (G2B) Model of E-governance can enhance local government revenue and boast local development in Cameroon. The paper ends with an in-depth analysis of the opportunities and constraints of digitalization of service delivery by local councils in Cameroon.